Study on thermal performance of microchannel heat sinks with periodic jetting and throttling structures in sidewalls. (25th July 2019) - Ma, D.D.; Xia, G.D.; Wang, W.; Jia, Y.T.; Yang, Y.C.
Highlights: Novel offset throttling and jetting microchannel is designed. Throttling channel is reduced at the same pumping power. Throttling channel reduces the required flow rates and pumping power. With increasing of flow rates, heat transfer enhancement is weakened. Effects of heat power on pressure drops is less, but larger for temperature. Abstract: An experimental investigation has been carried out to analyze the flow and heat transfer characteristics in the silicon microchannel heat sinks with periodic jetting or throttling structures by using deionized water with flow rates of 28–95 ml/min. The heat sink includes 10 parallel microchannel with 49 identical units (jetting or throttling structures) long the flow direction, width of 100–200 μm, depth of 215 μm. Results show the heat transfer of throttling microchannel heat sink is enhanced obviously albeit with larger pressure drop penalty. It is because that the fluid is completely blocked by the sudden contractible structure, then forms the severe reflux to wash divergent structure and enhance fluid mixing. Compared with jetting microchannel heat sink, the Nu av of throttling microchannel heat sink is improved to 1.56–1.29 times albeit with f increased to 1.84–1.51 times with increasing of flow rates. But the total performance evaluation criterion (PEC) is increased to about 2.5 times. For maximum temperature <60 °C, the required minimum flow rates of throttling microchannel heat sink are reduced obviously. Even the pumping power of that is increased at heater power larger than 50 W, the thermal resistance is reduced severely. It means the throttling microchannel heat sink can meet larger heater power with lower flow rates in application.